2017 International Conference on Asian Language Processing (IALP) 2017
DOI: 10.1109/ialp.2017.8300572
|View full text |Cite
|
Sign up to set email alerts
|

Improving character-level Japanese-Chinese neural machine translation with radicals as an additional input feature

Abstract: In recent years, Neural Machine Translation (NMT) has been proven to get impressive results. While some additional linguistic features of input words improve wordlevel NMT, any additional character features have not been used to improve character-level NMT so far. In this paper, we show that the radicals of Chinese characters (or kanji), as a character feature information, can be easily provide further improvements in the character-level NMT. In experiments on WAT2016 Japanese-Chinese scientific paper excerpt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…For Japanese-Chinese translation, Zhang et al proposed the following three data augmentation methods to improve the quality of Japanese-Chinese NMT: (1) radicals as an additional input feature [25]; (2) the created Chinese character decomposition table [26]; (3) a corpus augmentation approach [27], considering the lack of resources in bilingual corpora.…”
Section: Guokun Et Al Automatically Built a Corpus By Crawling Langua...mentioning
confidence: 99%
See 1 more Smart Citation
“…For Japanese-Chinese translation, Zhang et al proposed the following three data augmentation methods to improve the quality of Japanese-Chinese NMT: (1) radicals as an additional input feature [25]; (2) the created Chinese character decomposition table [26]; (3) a corpus augmentation approach [27], considering the lack of resources in bilingual corpora.…”
Section: Guokun Et Al Automatically Built a Corpus By Crawling Langua...mentioning
confidence: 99%
“…Corpus linguistics [3] Japanese-Chinese bilingual corpora [1], TED talks, [4,5] Web-crawled corpora [7][8][9][10][11]13,14,16,17,19,24] Other corpora [6,12,18,[20][21][22] Corpus augmentation [15,23,[25][26][27] The above related research showed that corpora play an important role in improving translation accuracy and in other directions of language processing. Thus, the construction of a Japanese-Chinese bilingual corpus for NMT has significant implications for the resource scarcity problem.…”
Section: Classification Related Workmentioning
confidence: 99%
“…Our approach is motivated by the work of NMT incorporated with linguistic input features . Chinese linguistic features, such as radicals and Pinyin, have been demonstrated effective to Chinese-sourced NMT (Liu et al, 2019;Zhang and Matsumoto, 2017;Du and Way, 2017) and Chinese ASR (Chan and Lane, 2016). We also incorporate Pinyin as an additional input feature in the robust NMT model, aiming at improving the robustness of NMT further.…”
Section: Baselinementioning
confidence: 99%
“…Our approach is motivated by the work of NMT incorporated with linguistic input features . Chinese linguistic features, such as radicals and Pinyin, have been demonstrated effective to Chinese-sourced NMT Zhang and Matsumoto, 2017;Du and Way, 2017) and Chinese ASR (Chan and Lane, 2016). We also incorporate Pinyin as an additional input feature in the robust NMT model, aiming at improving the robustness of NMT further.…”
Section: Baselinementioning
confidence: 99%